Management Forecasts in Japan: An Empirical Study of Forecasts that Are Effectively Mandated - Kato, Kazuo; Skinner, Douglas J.; Kunimura, Michio (The Accounting Review, 2009)
ABSTRACT: We study management forecasts in Japan, where forecasts are effectively mandated but managers have considerable latitude over the numbers they release. We find that managers' initial earnings forecasts for a fiscal year are systematically upward-biased but that they revise their forecasts downward during the fiscal year so that most earnings surprises are non-negative. Managers' initial forecast optimism is inversely related to firm performance, and is more pronounced for firms with higher levels of insider ownership, smaller firms, and firms with a history of forecast optimism. The fact that managers' forecasts tend to be consistently optimistic suggests that reputation effects are insufficient to ensure managerial forecast accuracy. We also find that the information content of managers' forecasts is related to proxies for whether market participants view the forecasts as credible.